Keputusan Pembelian Kosmetik Halal di Kalangan Generasi Z Muslim - Agustina, Alvi Khoiriah; Musyafa', Musyafa' (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the effect of halal lifestyle, halal awareness, religiosity, and product quality on purchasing decisions for halal cosmetics for Generation Z Muslims in Jepara Regency. This generation has explorative, critical, and highly connected characteristics with the digital world, which is both an opportunity and a challenge for the development of the halal cosmetics industry. The research was conducted in Jepara Regency using a quantitative approach. The sample consisted of 100 respondents selected through purposive sampling method based on certain criteria, namely generation Z who are Muslim, domiciled in Jepara Regency, and have purchased halal cosmetics. Data collection was carried out using an online questionnaire, and data analysis using multiple linear regression with SPSS Statistics 20 software. The results showed that the four independent variables had a positive and significant influence on purchasing decisions. Halal awareness has the most dominant influence with a regression coefficient of (0.441), followed by halal lifestyle (0.331), religiosity (0.280), and product quality (0.189). Overall, this research model is able to explain 60% of the variation in purchasing decisions for halal cosmetics, while the remaining 40% is influenced by other factors not examined. This research contributes to the development of consumer behavior literature and offers practical insights for manufacturers in designing appropriate marketing strategies.